Linking Person-Job Fit and Perceived Organization Support to Increase Public Employee Performance: The Role of Innovative Behavior in Workplace - Suryosukmono, Gerry; Praningrum, Praningrum; Pareke, Fahrudin Js (Department of Management, Faculty of Economics and Business, Brawijaya University, 2022)
This study aims to examine and analyze the effect of P-J fit and perceived organizational support on task performance mediated by innovative behavior. This study provides empirical evidence regarding the role of innovation in increasing the fit between a person and his work and organizational support in improving task performance. The population of this study is civil servants who work in the Bengkulu Provincial Government, one of the largest province in West Part of Indonesia. The number of respondents taken amounted to 155 people. This study uses the Structural Equation Modeling (SEM ) method using the Partial Least Square (PLS) method with SmartPLS software application version 3.0. The study concludes that P-J fit positively affects organizational commitment and task performance based on the research conducted. The perceived support factor from the organization also affects innovative behavior and task performance. In a mediating relationship, P-J fit mediated by creative behavior will affect task performance. However, this study found that the ties built by P-J fit on task performance directly had a more significant effect than when mediated by innovative behavior. Organizational support mediated by creative behavior also improves task performance, although not as big as the direct effect of organizational support on employee performance. This research also contributes to the development of social exchange theory by using the innovation factor as a supporter.